Pengaruh Kerja Sama Tim, Motivasi Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan pada Mie Gacoan Cabang Sidoarjo - Affandi, M Yusuf; Andriani, Dewi; Sumartik, Sumartik (Universitas Batanghari Jambi, 2025)
This study was conducted to determine and test the effect of teamwork, work motivation and work environment on employee performance at Mie Gacoan Sidoarjo branch. The research data were collected through questionnaires with simple random sampling with a minimum of 126 respondents. This study used a quantitative method of multiple linear regression analysis. The results of the study showed that simultaneously and partially there was a positive and significant influence between the variables of teamwork, work motivation and work environment on employee performance at Mie Gacoan Sidoarjo Branch.